Miniriset Hukum Agraria Kepastian Hukum Atas Tanah Kosong di Kota Medan - Filzah Irshadi; Feby Adelia Parhusip; Cindy Nababan; Dian Wahyu Harmoni Sembiring (Lembaga Pengembangan Kinerja Dosen, 2024)
Land has a fundamental role in the life of every citizen. Its importance can be seen from the enthusiasm of individuals in acquiring and maintaining land as a gift from God Almighty. As an agricultural country, Indonesia recognizes the importance of land as a source of people's welfare and as a foundation for industrial, agricultural and residential activities. Land issues are complex, especially after independence, with the dualism of agrarian law between colonial law and customary law. To overcome this, the government implemented Law Number 5 of 1960 concerning Agrarian Affairs, which eliminated this dualism and made Customary Law the material basis. This is in line with the principle of unified agrarian law for all regions of Indonesia. However, the issue of land control, especially vacant land or state land, creates legal uncertainty. Clarity of regulations is needed that provide legal protection for individuals who use land with good intentions, confirming the ownership status of the land. This is important so that the use of land for subsistence needs can be regulated legally, maintaining a balance between state interests and individual rights